Force distribution is more important than its intensity! - Alberto Consolaro (Dental Press Editora, 2014)
A common question about root resorption is raised in orthodontic practice: What is more important, the intensity of force or its distribution along the root, periodontal and alveolar structures? Diffuse distribution of forces applied to periodontal tissues during tooth movement tends not to promote neither extensive areas of cell matrix hyalinization nor significant death of cementoblasts that lead to root resorption. However, focal distribution or concentration of forces within a restricted area - as it occurs in tipping movements, even with forces of lower intensity - tend to induce extensive areas of hyalinization and focal death of cementoblasts, which is commonly associated with root resorption. In tipping movements, the apical regions tend to concentrate more forces in addition to wounding the cementoblasts due to the smaller dimension of their root structure as well as their cone shape. For this reason, there is an increase in root resorption. In the cervical region, on the other hand, the large area resulting from a large diameter and bone crown deflection tends to reduce the effects of forces, even when they are more concentrated, thus rarely inducing death of cementoblasts and root resorption.